Improved Functional Capacity Evaluation Performance Predicts Successful Return to Work One Year After Completing a Functional Restoration Rehabilitation Program. Issue 4 (5th October 2014) - Fore, Lisa; Perez, Yoheli; Neblett, Randy; Asih, Sali; Mayer, Tom G.; Gatchel, Robert J.
Abstract: Objective: To evaluate whether functional capacity evaluation (FCE) scores are responsive to functional restoration treatment, and to assess the ability of FCEs at program discharge to predict work outcomes. Design: An interdisciplinary cohort study of prospectively collected data. Setting: A functional restoration center. Patients: A consecutive sample of 354 patients with chronic disabling occupational musculoskeletal disorders (CDOMDs) completed a functional restoration program consisting of quantitatively directed exercise progression and multi‐modal disability management with interdisciplinary medical supervision. Methods: Each patient participated in an FCE at admission and discharge from treatment. The results of each FCE yielded the physical demand level (PDL) at which patients were functioning. Patients were initially divided into 5 PDL groups, based on job‐of‐injury lifting, carrying, and pushing/pulling requirements, for the pre‐ to posttreatment responsiveness analyses. Patients were subsequently divided into 5 PDL groups, based on their performance on the FCE upon program completion. Main Outcome Measures: Outcome measures included admission‐to‐discharge changes in PDLs and 2 specific FCE lifting tasks: isokinetic lifting; and the Progressive Isoinertial Lifting Evaluation (PILE). Socioeconomic outcomes were also evaluated, including post‐discharge work return and work retention 1‐year after treatment completion. Results: Overall, 96% of the patients demonstrated improvement in their PDLs from admission to discharge. A majority of patients (56%) were able to achieve a discharge PDL that was comparable to their estimated job‐of‐injury lifting requirement or higher ( P < .001). Lifting ability improved from admission to discharge by approximately 50% (all P < .001). Discharge PDLs predicted both work return ( P < .001) and work retention ( P < .001) 1 year later. Conclusions: FCE scores were responsive to functional restoration treatment, and the associated discharge PDLs predicted work return after treatment completion and work retention 1 year later.